Pemanfaatan Tepung Labu Kuning (Cucurbita Moschata Duchesne) sebagai Substituen Tepung Beras pada Pembuatan Baby Puff: [Utilization of Pumpkin Flour (Cucurbita Moschata Duchesne) as A Constituent of Rice Flour in Making Baby Puff] - Cornelia, MT, Dr. Ir. Melanie; Maulani, Heidi (Universitas Pelita Harapan, 2025)
Pumpkin was one of Indonesian agricultural product and known as a good source of carrotenoids such as β-carotene. β-carrotene was one of vitamin A precursor for human body and good for children’s growth. In this research, pumpkin flour made by two methods, by soaking in sodium metabisulfite solution 0,25% and with no treatment as control. This treatment can preserve β-carrotene value during heating process. The objective of this research were to determine the best method on producing pumpkin flour and to study its physical characteristic, β-carotene, dietary fiber, hardness, color and proximate analysis of chosen baby puff using pumpkin flour as its substitute. The result show that the best method of pumpkin flour was soaking in sodium metabisulfite solution 0,25%. The best pumpkin flour has characteristic 35,24µg/g of β-carotene, 4,62% dietary fiber, 66,7 ohue, 407,67% water holding capacity, and 0,63 gr/ml density. The best baby puff formulation based on physical, chemical analysis and organoleptic score was 5 % pumpkin flour subtitution. Its contain 24,6 µg/g of β-carotene, 5,12% of dietary fiber, 79,86 ohue and 493,00 g hardness. The highest amount of β-carotene was found in baby puff with 20% pumpkin flour subtitution Bahasa Indonesia Abstract: Labu kuning merupakan hasil pertanian Indonesia yang dikenal sebagai sumber zat gizi berupa β-karoten. β-karoten adalah salah satu prekursor vitamin A bagi tubuh manusia dan baik untuk pertumbuhan anak. Pada penelitian ini, tepung labu kuning dibuat dengan dua metode, yaitu perlakuan perendaman dalam larutan natrium metabisulfit 0,25% dan tanpa perlakuan sebagai kontrol. Perlakuan ini dapat mempertahankan nilai β-karoten selama proses pemanasan. Tujuan penelitian ini adalah untuk menentukan metode terbaik yaitu perendaman pada pembuatan tepung labu kuning berdasarkan sifat fisik, β-karoten, dan analisis proksimat tepung labu kuning terpilih dilihat dari β-karoten, serat pangan, kekerasan dan warna tepung labu kuning dan menggunakan tepung labu kuning sebagai substitusi. Hasil penelitian menunjukkan bahwa metode pembuatan tepung labu kuning terbaik adalah perendaman dengan larutan natrium metabisulfit 0,25%. Tepung labu kuning terbaik mempunyai data analisis β-karoten 35,24µg/g, serat pangan 4,62%, daya ikat air 407,67%, dan berat jenis 0,63 gr/ml. Formulasi baby puff terbaik berdasarkan analisis fisik dan kimia serta skor organoleptik adalah subtitusi tepung labu kuning 5%. Kandungan β-karotennya 24,6 µg/g, serat pangan 5,12%, kekerasan 493,00 g. Kandungan β-karoten tertinggi terdapat pada baby puff dengan subtitusi tepung labu kuning 20%